2022
DOI: 10.1371/journal.pone.0268080
|View full text |Cite
|
Sign up to set email alerts
|

Malaria transmission in Africa: Its relationship with yellow fever and measles

Abstract: Background Malaria has been strongly linked to the transmission and pathophysiology of some viral diseases. Malaria and vaccine-preventable diseases often co-exist in endemic countries but the implication of their co-existence on their transmission dynamics and control is poorly understood. The study aims to evaluate the relationships between the incidence of malaria and cases of measles and yellow fever in Africa. Methods The malaria incidence, death due to malaria, measles and yellow fever data were source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Projection model indicated, with 93.0% certainty (95% confidence interval: 92.7-93.2%) that YF mortality in Africa is expected to increase significantly by 2050. due to climate change [36]. Another environmental factor is the malaria mosquito control programs that also impact other breeds of mosquitoes [37]. This suggests that public health measures used to control mosquito-causing malaria (e.g., widespread deployment of insecticidetreated bed nets) could impact the occurrence of YF and vice versa [37,38] More specially, Uganda is experiencing a steady rise in temperature and variabilities in rain fall pattern.…”
Section: One Health Domains and Yf In Ugandamentioning
confidence: 99%
See 1 more Smart Citation
“…Projection model indicated, with 93.0% certainty (95% confidence interval: 92.7-93.2%) that YF mortality in Africa is expected to increase significantly by 2050. due to climate change [36]. Another environmental factor is the malaria mosquito control programs that also impact other breeds of mosquitoes [37]. This suggests that public health measures used to control mosquito-causing malaria (e.g., widespread deployment of insecticidetreated bed nets) could impact the occurrence of YF and vice versa [37,38] More specially, Uganda is experiencing a steady rise in temperature and variabilities in rain fall pattern.…”
Section: One Health Domains and Yf In Ugandamentioning
confidence: 99%
“…Another environmental factor is the malaria mosquito control programs that also impact other breeds of mosquitoes [37]. This suggests that public health measures used to control mosquito-causing malaria (e.g., widespread deployment of insecticidetreated bed nets) could impact the occurrence of YF and vice versa [37,38] More specially, Uganda is experiencing a steady rise in temperature and variabilities in rain fall pattern. More rainfalls are observed during the dry season.…”
Section: One Health Domains and Yf In Ugandamentioning
confidence: 99%
“…It should also be noted that African population is more at risk of contracting the yellow fever virus and of developing severe forms and death due to a low rate of vaccination coverage and daily activities that bring them closer to vectors such as agriculture, livestock, hunting, and deforestation [77][78][79][80]. Also, the existence in Africa of other health conditions such as malnutrition, tuberculosis, malaria and, HIV are other factors that could be associated with this high of YFV CFR [81][82][83]. About 1/5 th (18.8%) of sampled human participants included in this review had IgG antibodies against YFV (past infection).…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Plasmodium spp. belong to the apicomplexan parasites with a complex life cycle involving two hosts, an invertebrate, the Anopheles mosquito acting as its biological vector and a vertebrate, such as humans [ 19 , 20 ]. It has been found that the complement is involved in all life cycle-stages of the Plasmodium parasites, including the pre-erythrocytic-, erythrocytic-, and sexual-stages during immunity against malaria [ 7 , 21 , 22 ].…”
Section: Parasite’s Complement Regulatory and Evasion Moleculesmentioning
confidence: 99%